“Prayer in the Garden”, by Bernardo Bitti S. J. in Rondoncan - Tejada Farfán, Andrea Giuliana (2023)
The present article has as a main objective to carry out an iconographic and iconological analysis of the work Prayer in the Garden of the Jesuit painter Bernardo Bitti, belonging to the only series of eight canvases that remains of his authorship, about The main mysteries of the life, and death of Christ our Savior and the Holy Virgin Mary, his mother,which he painted for the transfiguration college church at the end of 16th century and which is currently located in Saint Thomas Aquinas church in the district of Rondocan, province of Acomayo, Cuzco. Also, it is denoted an approach to the visual sources that brother Bernardo may have used for the composition of this painting. Furthermore, in light of the recent discovery, it is disassociated of the homonymous canvas that remains in the National Museum of Archaeology, Anthropology and History of Peru, from the series of eight canvases that Bernardo Bitti painted for the Jesuit church in Cuzco. In addition, through file documents, particularly the manuscript signed by himself containing the statement of his last vows, a more accurate chronology of the two stays of the painter camerte in said city is proposed.